The Luftwaffe : creating the operational air war, 1918-1940 - Corum, James S. (Lawrence : University Press of Kansas, 1997)
This study provides an appraisal of Germany's air forces from the post-World War I era through the early stages of World War II. The author demolishes several myths surrounding the Luftwaffe, including the belief that they had no ideas beyond the support of ground forces.
Introduction -- The lessons of World War I -- Response to disarmament : Von Seeckt and Wilberg -- Preparation for aerial rearmament -- Theory and air doctrine in the Wever era, 1933-1936 -- Air organization and technology in the Wever era, 1933-1936 -- The Luftwaffe in the Spanish Civil War, 1936-1939 -- The Luftwaffe prepares for war : problems with leadership and organization -- Conclusion.
Includes bibliographical references (pages 345-368) and index.
Keywords: Germany. -- Luftwaffe -- History; 1900-1999; Geschichte 1918-1940; Maneuver warfare -- History -- 20th century; Air power -- Germany -- History; Aeronautics, Military -- Germany -- History; Air power -- Germany -- History; Germany -- Luftwaffe -- History; Germany // Luftwaffe -- History